Reading Realness - Oishi, Eve (A Companion to Contemporary Documentary Film, 2015)
This essay performs a critical comparison of two documentary films about queer and trans people of color, Jennie Livingston's Paris is Burning (1991) and Wu Tsang's Wildness (2012) and examines how the two films negotiate of the politics of representing reality and “realness.” The comparison illuminates two entwined problematics: the ways in which the challenges faced by each film are emblematic of the larger historical context in which they were made, specifically notions of queer community and its subjects; and the ways in which the negotiation of these challenges occurs in relation to a broader field of ethical and formal questions relating to documentary itself.
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 5-Auteur.rice noir.e; 5-Créateur.rice LGBTQ+; _Nettoyé